NEET persistence : Analysis of heterogeneity in the state dependence of the NEET situation - Sirniö Outi; Jernström Laura; Eskelinen Niko; Kauppinen Timo (Center for Open Science, 2025)
The vulnerable status of young people and their inadequate integration during entry into the labor market has been shown to increase the risk of several unfavorable outcomes in adulthood. In this study, we provide a longitudinal perspective to the labor market integration of young people by analyzing the dynamics of being a young Not in Employment, Education or Training (NEET). We focus on entry to and persistence of the NEET situation across time, namely genuine state dependence, by using correlated dynamic random-effects logit models to study the effect of the past on the current NEET situation. We analyze longitudinal individual-level data covering the full population living in Finland with a follow-up from age 18 till age 29 from 1995 till 2020. Our findings suggest clear state dependence in the NEET situation: being NEET in the previous year is associated with almost a 3-percentage-point increase in the probability of being NEET in the current year. We find that the state dependence of the NEET situation is moderately elevated for males and for those with lower parental educational attainment and considerably elevated for those with foreign origin or history of mental health issues or with child protection services.